圆柱齿轮减速器的优化设计 - 王德俊; 杨晓红; 李艳红; 刘洁 (Jixie chuandong)
Taking the smallest center distance of two-stage cylindrical gear reducer as objective,selecting the numbers of teeth,modulus,gear ratio and spiral angle as design variables,the mathematical model is established.The optimization design on gear reducer is carried out by using compound form and the optimization result is obtained.The result shows that,the optimization design based on compound form can gain more optimized results than the traditional ones.